Surgical Effectiveness of Prevention of Postoperative Purulent Complications in Children - Abdulxakimov A. R.; Xomidchonova Sh. X.; Xomidchonova Sh. X.; Xaidarov G. N. (International Journal of Scientific Trends, 2025)
Postoperative purulent complications (PGO) are one of the leading causes of worsening outcomes of surgical treatment in children. These complications can significantly slow down the recovery process, increase the length of hospital stay and require additional surgical intervention, which, in turn, increases the burden on the medical system and financial resources of healthcare. The problem of prevention of acute respiratory viral infections in children is especially relevant in the context of the high sensitivity of the child's body to infectious agents and the characteristics of their immune response. Effective prevention of complications requires an integrated approach that includes both infection prevention mechanisms and optimization of postoperative management of children. [1, 3, 5, 7].